2009
DOI: 10.1007/s00216-009-2800-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis of acoustically levitated drops by Raman spectroscopy

Abstract: An experimental apparatus combining Raman spectroscopy with acoustic levitation, Raman acoustic levitation spectroscopy (RALS), is investigated in the field of physical and chemical analytics. Whereas acoustic levitation enables the contactless handling of microsized samples, Raman spectroscopy offers the advantage of a noninvasive method without complex sample preparation. After carrying out some systematic tests to probe the sensitivity of the technique to drop size, shape, and position, RALS has been succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 26 publications
0
21
0
2
Order By: Relevance
“…A is the integrated intensity on the spectral band (squares excitation at 532 nm, circles excitation at 355 nm). Reprinted from Hopkins et al (2003) carried out by Tuckermann et al (2009). In this study, the CERS technique was applied to evaporating methanol droplets as well as droplets containing an aqueous solution of sodium ammonium sulfate (NH 4 ) 2 SO 4 solution which crystallizes during the droplet drying.…”
Section: Stimulated Raman Scattering Spectroscopymentioning
confidence: 99%
“…A is the integrated intensity on the spectral band (squares excitation at 532 nm, circles excitation at 355 nm). Reprinted from Hopkins et al (2003) carried out by Tuckermann et al (2009). In this study, the CERS technique was applied to evaporating methanol droplets as well as droplets containing an aqueous solution of sodium ammonium sulfate (NH 4 ) 2 SO 4 solution which crystallizes during the droplet drying.…”
Section: Stimulated Raman Scattering Spectroscopymentioning
confidence: 99%
“…10 Spectroscopy in combination with acoustic levitation has been used for airborne chemistry and protein crystallization by Santesson et al 11,12 Tuckermann et al used the backscattered Raman signal for chemical analysis of levitated drops. 13 Esen et al showed theoretically and experimentally the possibility of Raman scattering on deformed acoustically levitated droplets by a scattering angle of 90 • . 14 Yarin et al presented a method of calculation of the acoustic radiation pressure based on the boundary element method in Ref.…”
Section: Introductionmentioning
confidence: 98%
“…Spectroscopy in combination with acoustic levitation has been used for airborne chemistry and protein crystallization by [2], [15]. The backscattered Raman signal was used by [16] for the chemical analysis of levitated drops. [17] showed theoretically and experimentally the possibility of Raman scattering on deformed acoustically levitated droplets by a scattering angle of 90°.…”
Section: Introductionmentioning
confidence: 99%
“…The particle oscillation in the radial direction can lead to a dispersion of the Raman scattering intensity. [16], [17] obtained different intensity profiles for scanning in the radial and axial directions, which were attributed to the particle oscillations in the radial direction.…”
Section: Introductionmentioning
confidence: 99%